World Bank annual report 1998 (Washington D.C. : World Bank, 1998)
This annual report, which covers the period July 1, 1997, to June 30, 1998, has been prepared by the executive directors of both the International Bank for Reconstruction and Development, and the International Development Association in accordance with the respective by-laws of the institutions. This period saw changes such as: the implementation of the cost effectiveness review; further decentralization of decision-making powers to the field; a new budgeting and planning process for the first time linked to strategic objectives; and the introduction of a new human resources policy designed to end the traditional divisions between headquarters and local staff.
Includes index.
ne 13/03/2019
Ref
Keywords: World Bank; Economic development projects